Relative Doubt: Familial Searches of DNA Databases - Murphy, Erin (2010)
The continued growth of forensic DNA databases has brought about greater interest in a search method known as familial or kinship matching. Whereas a typical database search seeks the source of a crime-scene stain by making an exact match between a known person and the DNA sample, familial searching instead looks for partial matches in order to find potential relatives of the source. The use of a familial DNA search to identify the alleged Grim Sleeper killer in California brought national attention to the method, which has many proponents. In contrast, this Article argues against the practice of familial searching on a variety of grounds, including claims related to equality, accuracy, privacy, racial discrimination, and democratic accountability. It then addresses the legality of the method. Lastly, in the event that arguments to prohibit the practice prove unpersuasive, this Article sets forth recommendations for restrictions on familial searches that might ameliorate their possible iniquitous effects